Identification of triosephosphate isomerase as a novel allergen in Octopus fangsiao. (May 2017) - Yang, Yang; Chen, Zhong-Wei; Hurlburt, Barry K.; Li, Gui-Ling; Zhang, Yong-Xia; Fei, Dan-Xia; Shen, Hai-Wang; Cao, Min-Jie; Liu, Guang-Ming
Highlights: TIM from Octopus fangsiao was purified and identified as a novel allergen. Physicochemical and immunological characteristics of TIM were evaluated. The linear and conformational epitopes of TIM were elucidated and identified. Abstract: Octopus is an important mollusk in human dietary for its nutritional value, however it also causes allergic reactions in humans. Major allergens from octopus have been identified, while the knowledge of novel allergens remains poor. In the present study, a novel allergen with molecular weight of 28 kDa protein was purified from octopus ( Octopus fangsiao ) and identified as triosephosphate isomerase (TIM) by mass spectrometry. TIM aggregated beyond 45 °C, and its IgE-binding activity was affected under extreme pH conditions due to the altered secondary structure. In simulated gastric fluid digestion, TIM can be degraded into small fragments, while retaining over 80% of the IgE-binding activity. The full-length cDNA of O. fangsiao TIM (1140 bp) was cloned, which encodes 247 amino acid residues, and the entire recombinant TIM was successfully expressed in Escherichia coli BL21, which showed similar immunoreactivity to the native TIM. Different intensity of cross-reactivity among TIM from related species revealed the complexity of its epitopes. Eight linear epitopes of TIM were predicted following bioinformatic analysis. Furthermore, a conformational epitope (A71 G74 S69 D75 T73 F72 V67 ) was confirmed by the phage display technology. The results revealed the physicochemical and immunological characteristics of TIM, which is significant in the development of hyposensitivity food and allergy diagnosis.